2022
DOI: 10.24952/tijaroh.v8i2.5896
|View full text |Cite
|
Sign up to set email alerts
|

Determination of The Success of Muslim Women Ebtrepreneurs: The Conceptual Model

Abstract: Khadijah has set an example as a successful Muslim woman entrepreneur. However, specific research focusing on the success of Muslim female entrepreneurs is still limited. This study aims to identify the determinants of the success of Muslim women entrepreneurs and develop a conceptual model. Literature research data sourced from Google Scholar. Data collection using the publish or perish application. Data analysis used the preferred reporting items for systematic reviews and meta-analyses (PRISMA) approach. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Bahri, Ali, et al (2022) found that competency is one of the six factors determining the success of asnāf entrepreneurs. Competence is also one of the four dimensions of success for Muslim women entrepreneurs (Bahri, Wibowo, and Suyadi, 2022).…”
Section: The Role Of Talent For Entrepreneursmentioning
confidence: 99%
See 1 more Smart Citation
“…Bahri, Ali, et al (2022) found that competency is one of the six factors determining the success of asnāf entrepreneurs. Competence is also one of the four dimensions of success for Muslim women entrepreneurs (Bahri, Wibowo, and Suyadi, 2022).…”
Section: The Role Of Talent For Entrepreneursmentioning
confidence: 99%
“…Badal (2014) explains that determination is related to resilience in the face of difficult obstacles, even those that seem insurmountable. (Bahri, Wibowo, et al 2022) identified that business survival indicates entrepreneurial success.…”
Section: Talent As a Driver Of Success Of Entrepreneursmentioning
confidence: 99%